Reduction of gastroschisis using a surgical glove in the absence of standard silos - Mohammad Akbar Shirzad; Mohammad Tareq Rahimi; Reshadullah Jurat; Haseeb Rahman (Elsevier, 2020)
Gastroschisis is a congenital abdominal wall defect with incidence of 1 in 4000 live births. The primary goal of treatment is to reduce bowel back to the abdominal cavity with minimizing risk of injury to the bowel or increased intra-abdominal pressure. The problem with completely reducing the viscera in gastroschisis is related to the status of the bowel, especially when bowel loops are edematous and matted together. The main treatment options are primary closure or delayed closure with use of a silo. Here we are reporting a case of successful reduction of herniated viscera in a gastroschisis patient using surgical latex gloves as a silo in the absence of standard silos.